UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MODEL EXAMPLES NON EXAMPLES PADA MATERI POKOK BANGUN DATAR KELAS VI MIN KISARAN BERDASARKAN KULRIKULUM 2013 - Mapi lindo (Yayasan Akrab Pekanbaru, 2019)
This study aims to improve the learning outcomes of math students grade VI MIN Kisaran through the model of learning examples non examples, especially on the material wake flat. The type of this research is the research will not class (PTK) done in 4 stages of planning, implementation, observation, reflection. The study was conducted in 2 cycles with the object of the study of all students of class VI MIN Range year 2015/2016 which amounted to 40 students. The results showed that the model of learning examples non examples in improving students' understanding of the concept of mathematics lessons. Based on the results of the test cycle 1 results 40 students there are 27 people (67.5%) while 13 students (32.5%) has not reached mastery. While the second cycle of the results of 40 students there are 35 students (87.5%) who have (37.5%) have not reached learning mastery. Based on the results of the research, it can be concluded that through the model lesson examples non examples can improve mathematics learning outcomes of grade VI students MIN Kisaran especially in the material wake flat.